Modelling extreme market risk of Polish banks' debt instruments' portfolios - Łupiński, Marcin (Modelowanie wartości ekstremalnych ryzyka rynkowego portfeli papierów dłużnych znajdujących się w posiadaniu polskich banków, 2013)
The main goal of this article is to present extreme market risk evaluation methods which go beyond the standard Value at Risk methodology. Two main approaches: Expected Tail Loss (ETL) and Extreme Value Theory (EVT) are presented and then applied to simulate interest risk stemming from government debt portfolio held by Polish banks. The two methods seem to be very useful to estimate real market risk exposures during the times of distress on the financial markets.
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 113-130
Keywords: market risk; Value at Risk; Expected Tail Loss; Extreme Value Theory; ryzyko rynkowe